Chronic hyperammonemia causes a hypoglutamatergic and hyperGABAergic metabolic state associated with neurobehavioral abnormalities in zebrafish larvae - Probst, Joris; Kölker, Stefan; Okun, Jürgen G.; Kumar, Amrish; Gursky, Eduard; Posset, Roland; Hoffmann, Georg F.; Peravali, Ravindra; Zielonka, Matthias (Experimental neurology, 2020)
Chronic hyperammonemia is a common condition affecting individuals with inherited urea cycle disorders resulting in progressive cognitive impairment and behavioral abnormalities. Altered neurotransmission has been proposed as major source of neuronal dysfunction during chronic hyperammonemia, but the molecular pathomechanism has remained incompletely understood. Here we show that chronic exposure to ammonium acetate induces locomotor dysfunction and abnormal feeding behavior in zebrafish larvae, indicative for an impairment of higher brain functions. Biochemically, chronically elevated ammonium concentrations cause enhanced activity of glutamate decarboxylase isoforms GAD1 and GAD2 with increased formation of GABA and concomitant depletion of glutamate, ultimately leading to a dysfunctional hypoglutamatergic and hyperGABAergic metabolic state. Moreover, elevated GABA concentrations are accompanied by increased expression of GABAA receptor subunits alpha-1, gamma-2 and delta, supporting the notion of an increased GABA tone in chronic hyperammonemia. Propionate oxidation as major anaplerotic reaction sufficiently compensates for the transamination-dependent withdrawal of 2-oxoglutarate, thereby preventing bioenergetic dysfunction under chronic hyperammonemic conditions. Thus, our study extends the hypothesis of alterations in the glutamatergic and GABAergic system being an important pathophysiological factor causing neurobehavioral impairment in chronic hyperammonemia. Given that zebrafish larvae have already been successfully used for high-throughput identification of novel compounds to treat inherited neurological diseases, the reported zebrafish model should be considered an important tool for systematic drug screening targeting altered glutamatergic and GABAergic metabolism under chronic hyperammonemic conditions in the future.
Gesehen am 23.10.2020